Crystalline multicomponent compounds involving hexaammine cobalt(iii) cations. (27th May 2022) - Darii, Mariana; Beleaev, Ecaterina S.; Kravtsov, Victor Ch.; Bourosh, Paulina; Chumakov, Yurii; Hauser, Jürg; Decurtins, Silvio; Liu, Shi-Xia; Sultanova, Olga; Baca, Svetlana G.
Abstract : Among nine synthesized multicomponent compounds involving hexaammine cobalt(iii ) cations and N-, N, O- and O-donor organic moieties, the compound [Co(NH3 )6 ]Cl3 ·2(phen)·3H2 O shows the best biological activity against plant pathogenic bacteria. Abstract : A new series of multicomponent compounds containing the cation [Co(NH3 )6 ] 3+ and various organic N-, N, O-, and O-donor moieties has been synthesized and crystallized. The series involves [Co(NH3 )6 ]Cl3 ·2(phen)·3H2 O (1 ), [Co(NH3 )6 ](Hbdc)(bdc)·3H2 O (2 ), [Co(NH3 )6 ]Cl2 (Hpht)·3H2 O (3 ), [Co(NH3 )6 ]Cl(Hpht)2 ·3H2 O (4 ), [Co(NH3 )6 ]Cl(2, 3-pdc)·H2 O (5 ), [Co(NH3 )6 ]11 [Co(2, 5-pdc)3 ]8 Cl·84H2 O (6 ), [Co(NH3 )6 ][Co(3, 5-pdc)2 (H2 O)4 ]Cl·3H2 O (7 ), [Co(NH3 )6 ]Cl(sb)·4H2 O (8 ), and [Co(NH3 )6 ]2 (sb)3 ·EtOH·2.5H2 O (9 ) (where phen = 1, 10-phenanthroline, H2 bdc = diphenyl-4, 4′-dicarboxylic acid, H2 pht = o -phthalic acid, H2 pdc = 2, 3-/2, 5-/3, 5-pyridinedicarboxylic acid, H2 sb = 4-sulfobenzoic acid). Single crystal X-ray diffraction studies have revealed that in these compounds the [Co(NH3 )6 ] 3+ cation serves as a building block for the incorporation of various anions/molecules and promotes the formation of multicomponent compounds with extended charge-supported networks between cations and anions and others such as H-bonds between charged⋯neutral and neutral⋯neutral components as well as π–π stacking interactions. In addition to the [Co(NH3 )6 ] 3+ cations, compounds 1–9 contain in changing composition Cl −, deprotonated phthalate, diphenyldicarboxylate, pyridinedicarboxylate, and sulfonate anions or complex [Co(2, 5-pdc)3 ] 4− and [Co(3, 5-pdc)2 (H2 O)4 ] 2− anions, as well as neutral 1, 10-phenanthroline and ethanol and water molecules as components of the crystallization. Hirshfeld surface analysis was also performed to discuss the strength of hydrogen bonds and to quantify the inter-contacts. Energy decomposition analysis of the intermolecular interaction energy was performed using the SAPT method to study the non-covalent bonding interactions of [Co(NH3 )6 ] 3+ cations with mono-, dianions and neutral molecules, and it was found that the calculated bonding energy for compound 1 is minimal. Compounds 1–9 were tested in vitro against Rhizobium (Agrobacterium) vitis, an oncogenic bacterium that causes tumor formation in plants. Compound 1, comprising hexaammine cobalt(iii ) chloride and 1, 10-phenanthroline, showed the highest inhibitory potential and is thus qualified for an application against bacterial cancer in plants.